2005
DOI: 10.1007/s00125-005-1780-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the incidence of type 1 diabetes and maternal enterovirus antibodies: time trends and geographical variation

Abstract: Aims/hypothesis: We have previously observed an inverse correlation between the incidence of type 1 diabetes and enterovirus infections in the background population. The aim of this study was to analyse whether maternal enterovirus antibody status, which reflects both the frequency of enterovirus infections and the protection conferred by the mother on the offspring, also correlates with the incidence of type 1 diabetes. Methods: Maternal enterovirus antibodies were analysed from serum samples taken from pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 43 publications
3
85
0
1
Order By: Relevance
“…First, as an indication of a declining 'herd immunity' to enteroviruses, maternal antibody levels have decreased in many European countries over the past 20 years [20]. Second, the frequency of maternal antibodies to different enteroviruses is higher in countries with a low or intermediate incidence of type 1 diabetes than in countries with a high incidence of the disease [20], suggesting a relationship between low herd immunity to enteroviruses and high risk for type 1 diabetes development. Finally, high levels of maternal enterovirus antibodies in serum and breast milk correlate with a reduced frequency of such infections in children [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, as an indication of a declining 'herd immunity' to enteroviruses, maternal antibody levels have decreased in many European countries over the past 20 years [20]. Second, the frequency of maternal antibodies to different enteroviruses is higher in countries with a low or intermediate incidence of type 1 diabetes than in countries with a high incidence of the disease [20], suggesting a relationship between low herd immunity to enteroviruses and high risk for type 1 diabetes development. Finally, high levels of maternal enterovirus antibodies in serum and breast milk correlate with a reduced frequency of such infections in children [26].…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the observations linking enterovirus infections to the development of type 1 diabetes [1][2][3][4][5], it would be expected that such infections are more common in countries with a high disease incidence compared with those with an intermediate or low incidence. In contrast to this assumption, epidemiological studies conducted in different geographical regions of Europe have demonstrated that the frequency of enterovirus infections in the background population shows an inverse correlation to the incidence of type 1 diabetes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…11,12,22 In the present study we evaluated polio hypothesis by analyzing how frequently infants can experience enterovirus infections in the absence of maternal antibodies. Even though maternal antibodies were quite frequent in general, the results suggest that antibodies against certain serotypes can be relatively rare, especially in high titers (such as CBV5 and E9).…”
Section: Methodsmentioning
confidence: 99%
“…11,12 The development of IgA antibodies is regarded as a major advantage of orally administered live poliovirus vaccine vs. parenterally administered inactive virus vaccine. 2 According to our study 88% of children had IgA class poliovirus 1 antibodies by ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation